Rasio keuangan dan variasi harga saham: Bukti empiris dari perusahaan perbankan di bursa efek Indonesia - Gunawan, Daniel Vincent; Sugara, Kathryn (Nur Science Institute, 2024)
The stock price volatility of banking companies listed on the Indonesia Stock Exchange (IDX) is the subject of this study, which examines the possible influence of various factors on the level of volatility. Values such as Return on Assets (ROA), Dividend Payout Ratio (DPR), debt-to-equity ratio (DER), and loan-to-deposit ratio (LDR) are some of the criteria considered in this analysis. Various linear regression approaches collect and evaluate data methodically over time. The study's findings indicate that ROA and DPR significantly impact company prices; however, there is no definite relationship between LDR and DER and stock price performance. The regression model shows a strong correlation between the independent variables and stock prices, as evidenced by the R-squared value of 36%, indicating that including additional factors can improve the model's accuracy. This study aims to provide insight into managerial decision-making and underscores the need for further investigation into other factors influencing stock share prices.